The Misuse of Police Escorts and the Decline of Ethical Standards in Law Enforcement Institutions - Yonathan, Albertus Agung (Jurnal Ilmu Hukum Kyadiren, 2025)
The misuse of Patrol and Escort (Patwal) facilities by internal members of the Indonesian National Police (Polri) has sparked public controversy and contributed to the erosion of public trust in the police institution. This study aims to examine the legal provisions governing the Patwal function as outlined in Law Number 2 of 2002, identify applicable sanctions for abuses of authority, and assess the legal and sociological implications of such misconduct on the institutional image and legitimacy of the Polri. Employing a normative legal approach and a descriptive qualitative method, this study is based on an extensive review of legal literature and case analyses. The findings reveal that the misuse of Patwal facilities reflects systemic weaknesses in internal oversight, a lack of integrity among personnel, and the ineffectiveness of administrative, ethical, and criminal sanction mechanisms. These violations underscore a persistent gap between established legal norms and actual field practices, further deteriorating public perceptions of the professionalism of the police force. This study recommends comprehensive regulatory reform, enhanced supervisory mechanisms, and institutional restructuring as strategic measures to restore public confidence and promote a fair, transparent, and accountable system of law enforcement.